Revisiting Greenland ice sheet mass loss observed by GRACE - Schrama, E.J.O. (author); Wouters, B. (author) (Journal of Geophysical Research, 2011)
In this paper we discuss a new method for determining mass time series for 16 hydrological basins representing the Greenland system (GS) whereby we rely on Gravity Recovery and Climate Experiment (GRACE) mission data. In the same analysis we also considered observed mass changes over Ellesmere Island, Baffin Island, Iceland, and Svalbard (EBIS). The summed contribution of the complete system yields a mass loss rate and acceleration of ?252 ± 28 Gt/yr and ?22 ± 4 Gt/yr2 between March 2003 and February 2010 where the error margins follow from two glacial isostatic adjustment (GIA) models and three processing centers providing GRACE monthly potential coefficient sets. We describe the relation between mass losses in the GS and the EBIS region and found that the uncertainties in all areas are correlated. The summed contribution of Ellesmere Island, Baffin Island, Iceland, and Svalbard yields a mass loss rate of ?51 ± 17 Gt/yr and an acceleration of ?13 ± 3 Gt/yr2 between March 2003 and February 2010. The new regional basin reconstruction method shows that the mass loss within the southeastern basins in the GS has slowed down since 2007, while mass loss in western basins increased showing a progression to the north of Greenland. Space Engineering Aerospace Engineering